POSYANDU PROGRAM FOR THE ELDERLY AT THE RANTAU DISTRICT PUBLIC HEALTH CENTER REGENCY ACEH TAMIANG - Dwi Camelia; Nur Hafni; Bobby Rahman; Ti Aisyah; Aiyub (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study is a descriptive qualitative research that examines the Implementation of the Elderly Health Service Program at the Rantau Subdistrict Community Health Center (Puskesmas), Aceh Tamiang Regency. The focus of this research is to analyze the program's mechanism, its implementation, and the obstacles faced in providing elderly health services. This study employs Grindle's theory of policy implementation, which emphasizes that the success of implementation is influenced by the content of the policy and the context of its implementation. The method used in this research is descriptive qualitative with data collected through interviews, observations, and documentation. The data were analyzed by combining field findings with the theoretical framework. The results show that the elderly health program at the Rantau Subdistrict Puskesmas has been implemented through planning, organizing, implementation, and monitoring and evaluation, which are realized in activities such as the Elderly Clinic (Poli Lansia), Elderly Integrated Service Post (Posyandu Lansia), elderly gymnastics, health counseling, and home visits. The program implementation has followed the guidelines and increased elderly participation; however, it remains limited to basic health services. The main obstacles in implementation include a shortage of medical personnel, inadequate facilities and infrastructure, limited accessibility for elderly in remote areas, and suboptimal cross-sectoral coordination. Based on these findings, this research recommends strengthening the implementation mechanism through data-based planning, capacity building for health workers and elderly health cadres, provision of more complete health facilities and infrastructure, and the establishment of cross-sectoral coordination forums. Furthermore, the role of families and communities needs to be enhanced to support the sustainability of elderly health services.